A Case Study of Localized Juvenile Onset of Canine Demodecosis in a Male German Shepherd Dog (Global Journal of Science Frontier Research, 2018)
A ten-month old male German shepherd dog, named Tony was presented to the Himalayan Animal Rescue Trust (HART), Pokhara with the history of alopecia, itching, scratching and erythema over the facial region. Toney weighed 36 Kg, was black and brown in color. On clinical examination, the mucous membrane was found to be pink, and the body temperature was normal. The eczematous lesion was erythematous and alopecia in the area surrounding the lesions. The case was suspected of parasitic skin infection, and three deep skin scrapping were taken with the help of scalpel blade after moistening the skin with paraffin oil. The scraping was treated with few drops of KOH. The scab and matted hair were detached with the help of a clean needle. The sample was placed on a clean and dry microscopic glass slide and heated gently to soften the scab and clear the debris. A cover slip was placed, and it was examined first under the low power then high power for detail study. The larva and nymph of Demodex Canis were observed under the microscopic examination. The case was diagnosed as a localized juvenile onset of canine demodicosis.
Keywords: localized; juvenile; demodicosis; skin scrapings